Hidden Dangers of Ratus V Material for Reproductive Health - Nurhudhariani, Rose; Febriyanti, Siti Nur Umariyah (Health Notions, 2017)
This study aimed to explore the behavior of vaginal care Women Age Fertile in the city of Semarang. The research design used was descriptive qualitative with explanatory research approach. Purposive Sampling followed by Saturation is used in this study. The results of this study were 4 out of 5 informants using ratus v for vagina treatments to make the vagina to be rough, fragrant and reduce whiteness. The ratus-v material contains harmful chemicals that are lead and cadmium that can be a cancer-trigger. While one informant performs vaginal treatment using ozone at the clinic of obstetrician and obstetricians with safe tools, materials and techniques.